Local Strain Distribution in ZnO Microstructures Visualized with Scanning Nano X‐Ray Diffraction and Impact on Electrical Properties. Issue 11 (22nd November 2021) - Jordt, Philipp; Hrkac, Stjepan B.; Gröttrup, Jorit; Davydok, Anton; Krywka, Christina; Wolff, Niklas; Kienle, Lorenz; Adelung, Rainer; Magnussen, Olaf M.; Murphy, Bridget M.
Abstract : Three hexagonal ZnO rods, partly coated with gold or silver (Schottky contact) and aluminum (ohmic), are examined by current/voltage curves and scanning nano X‐ray diffraction. This combination revealed a striking impact of the crystalline quality on the Schottky contact properties. Further details can be found in the article number 2100201 by Bridget M. Murphy and co‐workers.